Examining the Influence of Secondary Math and Science Teacher Preparation Programs on Graduates' Instructional Quality and Persistence in Teaching - Danielle Marie Rhemer; Will Rogers; Sherry Ann Southerland (MDPI AG, 2024)
This quantitative, non-experimental study explored the relationship between the features of math and science teachers' preparation programs and their graduates' instructional rigor and persistence in teaching. Five math and science teacher preparation programs from across the United States were examined. Six sets of instructional tasks were collected from forty-six recent graduates of these programs to provide insights into novices' instructional rigor, and employment data were collected for thirty-seven of these graduates three to eight years after graduation. Regardless of the program's features, all teachers could design and implement instruction with moderate to high rigor. However, this ability was not the norm. Mixed-effect models suggest the strongest evidence between degree types (bachelor versus post-bachelor) was related to teachers' persistence: novices from graduate programs were more likely to persist in the work. However, no program feature was strongly associated with instructional rigor. Further research is needed to determine if the differences we found in teacher persistence are due to the nature of applicants drawn to particular programs (undergraduate versus graduate) or the program's structure. Future research is also needed to explore the influence of instructional context (i.e., district, school, and department norms for instruction) on math and science teachers' instructional rigor.